2022
DOI: 10.30935/cedtech/11482
|View full text |Cite
|
Sign up to set email alerts
|

Approaching the Use of Facebook to Improve Academic Writing and to Acquire Social Competences in English in Higher Education

Abstract: This article offers a proposal for integrating the social network Facebook into an English as a Foreign Language (EFL) classroom in tertiary education. The main objectives of this article are the following: 1. To offer a pedagogical proposal so that students can develop written skills and grammar at the same time that they acquire social competences using Facebook and 2. To know students' opinions about the use of Facebook and the main social competences that they have acquired while using this social network … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…Thus, Facebook can be used as one of the alternative platforms for online learning. Several studies found that Facebook can be used to conduct online teaching and learning [12]- [15]. Interestingly, several studies found that Facebook is the most suitable platform to support online learning and encourage students' engagement in discussion [14]- [16].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, Facebook can be used as one of the alternative platforms for online learning. Several studies found that Facebook can be used to conduct online teaching and learning [12]- [15]. Interestingly, several studies found that Facebook is the most suitable platform to support online learning and encourage students' engagement in discussion [14]- [16].…”
Section: Introductionmentioning
confidence: 99%
“…Similary, AlSaleem (2018) investigated the use of Facebook in enhancing students" oral communication skills. Moreover, Lirola (2021) used Facebook as a medium to improve students" academic writing and their acquisition of social competencies. Likewise, Sah (2015) investigated the effectiveness of using Twitter in ESL/EFL classroom and revealed that Twitter"s size restrictions on posts fosters creativity and improves students' collaborative skills as well as their language development.…”
Section: Introductionmentioning
confidence: 99%